1991
DOI: 10.1007/bf00193154
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to direct somatic embryogenesis in Medicago

Abstract: A highly efficient system for direct somatic embryogenesis is described. Leaf sections originating from young trifoliate leaves of Medicago falcata line 47/1-5 and Medicago sativa line No2/9R, directly produced embryos after cultivation in liquid B5IV induction medium. In comparison with indirect somatic embryogenesis the system omits the callus stage and thus allows shortening of the process of somatic embryogenesis in alfalfa by 35-40 days. It permits the avoidance of secondary changes occurring during the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(18 citation statements)
references
References 16 publications
1
16
1
Order By: Relevance
“…The stimulation of somatic embryogenesis in shoot apex or immature cotyledon caused by substituting fructose or maltose to sucrose as previously shown with Cl 830 (Loiseau et al, 1995), was confirmed here with 22 (Finer, 1987), Panax ginseng (CA Meyer) (Asaka et al, 1994) and for somatic embryo development in Picea mariana (Mill) BSP and Picea rubens Sarg (Tremblay and Tremblay, 1991). Sugars have acted as osmotic agent, at least in part, when their concentrations were high (Denchev et al, 1991;Tremblay and Tremblay, 1991 (Loiseau et al, 1995). In addition, sucrose, fructose or glucose at 168 mM reduced the production of somatic embryos compared to maltose at the same concentration in culture of immature cotyledons (Loiseau, 1996).…”
Section: Introductionsupporting
confidence: 86%
“…The stimulation of somatic embryogenesis in shoot apex or immature cotyledon caused by substituting fructose or maltose to sucrose as previously shown with Cl 830 (Loiseau et al, 1995), was confirmed here with 22 (Finer, 1987), Panax ginseng (CA Meyer) (Asaka et al, 1994) and for somatic embryo development in Picea mariana (Mill) BSP and Picea rubens Sarg (Tremblay and Tremblay, 1991). Sugars have acted as osmotic agent, at least in part, when their concentrations were high (Denchev et al, 1991;Tremblay and Tremblay, 1991 (Loiseau et al, 1995). In addition, sucrose, fructose or glucose at 168 mM reduced the production of somatic embryos compared to maltose at the same concentration in culture of immature cotyledons (Loiseau, 1996).…”
Section: Introductionsupporting
confidence: 86%
“…That media was successfully 11 used for Medicago sp. embryo development (8). Good results were also obtained for bean, but it was necessary the media to be optimized.…”
Section: Resultsmentioning
confidence: 99%
“…Next step was to transfer the embryos for l-2 weeks on solidified MS medium (15) supplemented with 10; 20; 30 and 40 ~tM ABA and 3 g gelrite for the maturation (8).…”
Section: Methodsmentioning
confidence: 99%
“…Among the auxins, the embryogenic effect of 2,4D is well known in legumes (2) and especially in genera Medic ago (32,10,17).…”
Section: Resultsmentioning
confidence: 99%